Chatbots and Scholarly Databases: Impressions from Trying Out Scopus AI. - Nogueira, Leticia Antunes (Information Technology & Libraries, 2025)
This viewpoint article explores Scopus AI--ElsevierS innovative add-on to the Scopus database--which allows users to engage with Scopus in natural language rather than via Boolean operators. Scopus Al's strength lies in combining the communication properties of a large language model with the information integrity of peer-reviewed sources. It does not substitute the need to review the literature but can be helpful in search, especially if stakes are low and a systematic approach is unnecessary. Because of increased sophistication of tools and information systems, the degree of competencies required from users also increases. Reasonable understanding of how AI works, as well as search expertise, a critical approach to source evaluation, and scientific skepticism remain essential. With these in place, and with a clear understanding of the purpose of various information tasks, users can be better positioned to decide how best to employ various tools to get the job done.